The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1088/0004-637x/712/2/1129
|View full text |Cite
|
Sign up to set email alerts
|

The Quasar Accretion Disk Size-Black Hole Mass Relation

Abstract: We use the microlensing variability observed for 11 gravitationally lensed quasars to show that the accretion disk size at a rest-frame wavelength of 2500 Å is related to the black hole mass by log(R 2500 /cm) = (15.78 ± 0.12) + (0.80 ± 0.17) log(M BH /10 9 M ). This scaling is consistent with the expectation from thin-disk theory (R ∝ M 2/3 BH ), but when interpreted in terms of the standard thin-disk model (T ∝ R −3/4 ), it implies that black holes radiate with very low efficiency, log(η) = −1.77 ± 0.29 + lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

74
487
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 346 publications
(563 citation statements)
references
References 85 publications
(189 reference statements)
74
487
2
Order By: Relevance
“…Gravitational microlensing (Chang & Refsdal 1979, 1984; see also Kochanek 2004 andWambsganss 2006) is the main tool used to estimate both parameters, either from time variability or through the wavelength dependence of the microlensing magnification. Microlensing studies (see e.g., Pooley et al 2007;Morgan et al 2010;Blackburne et al 2011Blackburne et al , 2014Blackburne et al , 2015Sluse et al 2011;Jiménez-Vicente et al 2012Hainline et al 2013;Mosquera et al 2013;MacLeod et al 2015) have found that the mean sizes of quasar accretion disks are roughly a factor of 2-3 greater than the predictions of the standard thin disk model. These differences are too large to be explained by contamination from the broad emission lines and the pseudo-continuum contributions, or scattering on scales larger than the accretion disk (Dai et al 2010;Morgan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gravitational microlensing (Chang & Refsdal 1979, 1984; see also Kochanek 2004 andWambsganss 2006) is the main tool used to estimate both parameters, either from time variability or through the wavelength dependence of the microlensing magnification. Microlensing studies (see e.g., Pooley et al 2007;Morgan et al 2010;Blackburne et al 2011Blackburne et al , 2014Blackburne et al , 2015Sluse et al 2011;Jiménez-Vicente et al 2012Hainline et al 2013;Mosquera et al 2013;MacLeod et al 2015) have found that the mean sizes of quasar accretion disks are roughly a factor of 2-3 greater than the predictions of the standard thin disk model. These differences are too large to be explained by contamination from the broad emission lines and the pseudo-continuum contributions, or scattering on scales larger than the accretion disk (Dai et al 2010;Morgan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Microlensing studies (see e.g., Pooley et al 2007;Morgan et al 2010;Blackburne et al 2011Blackburne et al , 2014Blackburne et al , 2015Sluse et al 2011;Jiménez-Vicente et al 2012Hainline et al 2013;Mosquera et al 2013;MacLeod et al 2015) have found that the mean sizes of quasar accretion disks are roughly a factor of 2-3 greater than the predictions of the standard thin disk model. These differences are too large to be explained by contamination from the broad emission lines and the pseudo-continuum contributions, or scattering on scales larger than the accretion disk (Dai et al 2010;Morgan et al 2010). Recent measurements of wavelength-dependent continuum lags in two local active galactic nuclei (AGNs) are consistent with the microlensing results (Shappee et al 2014;Edelson et al 2015;Fausnaugh et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We applied our model to single spectral band accretion disc size measurements made by Morgan et al (2010). The advantage of these data set is the existence of de-lensed fluxes that allow us to make independent mass accretion rate estimates.…”
Section: Apparent Disc Sizes For Objects With Known Fluxesmentioning
confidence: 99%
“…The advantage of these data set is the existence of de-lensed fluxes that allow us to make independent mass accretion rate estimates. We consider the sample from Morgan et al (2010) with the data for one object (Q J0158-4325) replaced by newer data from Morgan et al (2012), following our work in Abolmasov & Shakura (2012). Mass accretion rate was estimated using monochromatic delensed fluxes from Morgan et al (2010).…”
Section: Apparent Disc Sizes For Objects With Known Fluxesmentioning
confidence: 99%
See 1 more Smart Citation